Pengaruh Jenis Biofertilizer Terhadap Beberapa Parameter Fisika Kolam Gambut - Safutri, Dewi Noliyan; Hasibuan, Saberina; ', Syafriadiman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted from October to December 2016 in the Kualu Nenas village Tambang Distric Kampar Regency and in Environmental Quality Aquaculture, Faculty of Fisheries and Marine University of Riau. The objective of this research is to know the effect of biofertilizer type on change of soil physics properties and peat pond water such as the soil color, crude soil fiber, bulk density, soil porosity, temperature, turbidity and total suspended solid. The experimental design used a complete randomized design (CRD) with four treatments and three replications. The treatments applied were without biofertilizer (P0), biofertilizer from chicken manure (P1), biofertilizer from cow dung (P2), biofertilizer from human fecal (P3). The result of this study showed that P3 (biofertilizer from human fecal) was the best treatment for (crude soil fiber 47,1%; BD 0,45 g/cm3; and porosity 68%). For the turbidity and TSS, the best result in P0 (control). For the soil color of biofertilizer is no effected. The temperature of water that range from 26-300C. The range temperature is still quite good for aquatic organisms.Key words: Biofertilizer, Physical Parameter, Peat Land